2020
DOI: 10.1039/d0na00123f
|View full text |Cite
|
Sign up to set email alerts
|

Methanol-induced fast CsBr release results in phase-pure CsPbBr3 perovskite nanoplatelets

Abstract: A suitable minor amount of a methanol additive leads to bright, monodispersed and phase-pure 8 unit-cell-thick CsPbBr3 NPLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
(69 reference statements)
3
12
0
Order By: Relevance
“…We further noticed that a smaller amount of the Cs precursor relative to that of Pb led to the generation of CsPb 2 Br 5 (JCPDS No. 00-025-0211, see Figure S6 in the SI), which is in agreement with the previous observation by Liu et al 39 The comparison of PL spectra of the various powders indicated that the sample achieved using EtOH as the solvent and fixing the Cs/Pb ratio at 1:1.4 displayed the strongest PL intensity. We consequently chose this typical sample for further water-triggered morphology and phase transformation.…”
Section: ■ Introductionsupporting
confidence: 90%
“…We further noticed that a smaller amount of the Cs precursor relative to that of Pb led to the generation of CsPb 2 Br 5 (JCPDS No. 00-025-0211, see Figure S6 in the SI), which is in agreement with the previous observation by Liu et al 39 The comparison of PL spectra of the various powders indicated that the sample achieved using EtOH as the solvent and fixing the Cs/Pb ratio at 1:1.4 displayed the strongest PL intensity. We consequently chose this typical sample for further water-triggered morphology and phase transformation.…”
Section: ■ Introductionsupporting
confidence: 90%
“…59 According to the fitting data presented in Table S3, † the long-lifetime component (τ 2 ) of CsPbBr 3 was assigned to defect trapping-associated non-radiative recombination, while the short-lifetime (τ 1 ) originated from exciton radiative recombination. [61][62][63] It could be found that CsPbBr 3 -HBr and CsPbBr 3 -TMA/HBr possessed shorter radiative recombination lifetimes of 6.37 ns and 6.90 ns compared to that (7.18 ns) of CsPbBr 3 NCs, which were consistent with their higher PL.…”
Section: Resultssupporting
confidence: 57%
“…Color-saturated blue-emitting films with high carrier mobility are an essential part of light-emitting diodes (LEDs) and high-definition displays. Colloidal lead halide perovskite nanocrystals can easily be made by a low-cost solution-based synthesis and possess outstanding optical and electrical properties such as a tunable bandgap, narrow photoluminescence (PL) full width at half-maximum (fwhm), and wide color gamut, making them promising emitters for next-generation display applications. There are two main synthetic routes toward blue-emitting lead halide perovskites: (i) using mixed-halide Cl/Br-based perovskites; this approach has a drawback of emission red-shifts under bias due to ion migration; , or (ii) taking advantage of the quantum size effects in the solely Br-based nanocrystals, such as through the use of nanoplatelets (NPLs). Because of the highly ionic nature of lead halide perovskites, the ion migration in mixed-halide perovskites is hard to prevent, which makes Br-based perovskite nanomaterials more suitable candidates for the color-saturated blue light-emitting diodes (LEDs) with emission wavelength in the range of 455–465 nm.…”
mentioning
confidence: 99%